Beatles vs. Stones [large type] - McMillian, John Campbell (Center Point Large Print, 2013)
In the 1960s an epic battle was waged between the two biggest bands in the world -- the clean-cut, mop-topped Beatles and the bad boy Rolling Stones. Both groups liked to maintain that they weren't really "rivals" -- that was just a media myth, they politely said. Yet they plainly competed for commercial success and aesthetic credibility. On both sides of the Atlantic, fans often aligned themselves with one group or the other. In Beatles vs. Stones, John McMillian gets to the truth behind the ultimate rock and roll debate. Painting an eye-opening portrait of a generation dragged into an ideological battle between Flower Power and New Left militance, McMillian reveals how the Beatles-Stones rivalry was created by music managers' intent on engineering a moneymaking empire. He describes how the Beatles were marketed as cute and amiable, when in fact they came from hardscrabble backgrounds in Liverpool. By contrast, the Stones were cast as an edgy, dangerous group, even though they mostly hailed from the chic London suburbs. For many years, writers and historians have associated the Beatles with the gauzy idealism of the "good" sixties, placing the Stones as representatives of the dangerous and nihilistic "bad" sixties. Beatles vs. Stones explodes that split, ultimately revealing unseen realities about the turbulent sixties through its most potent personalities and its most unforgettable music.